2006
DOI: 10.1158/0008-5472.can-05-4451
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Promotes Invasion in Tumorigenic but not in Nontumorigenic Human Prostatic Epithelial Cells

Abstract: Transforming growth factor-B (TGF-B) is a pleiotropic growth factor with actions that are dependent on circumstances, including dose, target cell type, and context. TGF-B can elicit both growth-promoting and growth-suppressive activities. In normal tissues, TGF-B generally acts to restrict growth and maintain differentiation. However, during tumorigenesis, changes in TGF-B expression and cellular responses can promote tumorigenesis. The present study examines the effects of TGF-B on the nontumorigenic human pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 55 publications
6
107
1
Order By: Relevance
“…A change in the cellular response to TGF-b is frequently observed in cancer, and there is great interest in the molecular mechanisms responsible for the switch of TGF-b signalling from tumor suppression to tumor promotion (Bierie and Moses, 2006;Inman, 2011). TGF-b1 inhibits proliferation of RWPE-1 cells and BPH-1 benign prostate epithelial cells (Ao et al, 2006), but does not affect proliferation of metastatic PC3 cells or transformed derivatives of BPH-1, where instead it promotes an epithelial-to-mesenchymal transition (Ao et al, 2006;Zhang et al, 2009). An important TGF-b target gene, PMEPA1, has been implicated in this TGF-b switch (Singha et al, 2010), and silencing of PMEPA1 has been shown to reduce RWPE-1 cell proliferation (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A change in the cellular response to TGF-b is frequently observed in cancer, and there is great interest in the molecular mechanisms responsible for the switch of TGF-b signalling from tumor suppression to tumor promotion (Bierie and Moses, 2006;Inman, 2011). TGF-b1 inhibits proliferation of RWPE-1 cells and BPH-1 benign prostate epithelial cells (Ao et al, 2006), but does not affect proliferation of metastatic PC3 cells or transformed derivatives of BPH-1, where instead it promotes an epithelial-to-mesenchymal transition (Ao et al, 2006;Zhang et al, 2009). An important TGF-b target gene, PMEPA1, has been implicated in this TGF-b switch (Singha et al, 2010), and silencing of PMEPA1 has been shown to reduce RWPE-1 cell proliferation (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of EMT induction to other human prostate epithelial cells. For example, tumorigenic sublines of BPH-1 but not the parental non-malignant BPH-1 line could be induced to undergo EMT upon stimulation by TGF-β [37]. Nonmalignant BPH-1 cells with over-expression of snail, however, were shown to assume EMT and invasive phenotype in 3D cultures [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, as cancer progresses, TGF-h takes on a tumorigenic role, inducing angiogenesis, suppressing apoptotic activity, or enhancing cell motility (19)(20)(21)(22). Target cells respond to TGF-h through a number of specific downstream signaling pathways.…”
Section: Introductionmentioning
confidence: 99%